Emancipação, a cena e o espectador em jogo - Mostaço, Edelcio (Sala Preta, 2013)
The article isfocused in Bernard Dort and Jacques Rancière articulations around emancipation concept. If after 1980' scene was taken for the first as in the emancipation ways, these poetic articulations invite the spectator to experiment other senses and dispositions that can lead to other social interaction ways, as thought by Rancière. Now, by the senses of roles play.